Biochar use in agriculture as a nature-based solution: factors influencing N2O emissions in tropical soils - Gabetto, Fernanda Palmeira (2023)
The use of biochar as a soil amendment has recently gained attention due to its benefits associated with soil carbon (C) sequestration and mitigation of nitrous oxide (N2O) emissions. Although several studies have observed soil N2O emissions decrease in response to biochar application, explaining the cause-and-effect relationship remains challenging. In addition to this knowledge gap, there is a shortage of data obtained in tropical environments. In this context, this study was developed to assess the effect of biochar application on soil N2O emissions in tropical conditions and how different factors can influence this response. Therefore, the first experiment was conducted to evaluate the effects of converting sugarcane straw into biochar, comparing straw-covered soils with the two application rates (5 and 10 Mg ha-1) of straw-based biochar. In addition, we also focused on unraveling how biochar might affect these emissions through the quantification of N-related functional genes (AOA, AOB, nirK, nirS, nosZ). Our results revealed that applying sugarcane straw-based biochar to the soil decreased N2O emissions by 73% compared to straw-covered soils. However, this reduction was due to the N2O emissions increase caused by the straw presence, as the biochar application at both 5 and 10 Mg ha-1 rates exhibited similar results to the application of N fertilizer alone. The rise in N2O emissions under soils covered with straw had a strong positive interaction with the AOB relative abundance, which seems to be a significant N2O source from nitrification under tropical soils. Nevertheless, the biochar application rates of 5 and 10 Mg ha-1 appeared to be insufficient for N2O mitigation; therefore, a 20 Mg ha-1 rate was adopted for the following experiment. In the second experiment, we sought to determine the influence of different types of biochar produced from sugarcane (Saccharum spp.) straw (SB) and bagasse (BB), together with Pinus spp. and Eucalyptus spp. residues on soil N2O emissions. For a more precise physicochemical characterization, the different types of biochar were also examined through scanning electron microscopy (SEM), dispersive X-ray spectroscopy (EDS), and X-ray photoelectron spectroscopy (XPS). In this experiment, we observed the biochar capacity to suppress N2O emissions driven by N fertilizer use. Our results showed that the magnitude of this mitigation capacity varied with the feedstock biomass, where SB, BB, PB, and EB decreased soil N2O emissions by 50, 35, 35, and 25%, respectively. Among the evaluated treatments, only SB expressed a higher capacity to decrease N2O emissions than EB, which also had the highest share of hydroxyl/ether (CO) functional groups on its surface. Furthermore, biochars from forestry residues had more C in its surface composition, resulting in higher soil C contents. The application of PB was the best option among the forestry biomasses, as it decreased soil N2O emissions to levels similar to SB and BB while promoting higher soil C input. Our results validate that the biochar use as a soil amendment can be considered a win-win strategy, as it enhances soil C stocks while decreasing N2O emissions. However, the magnitude of this response relies on the biochar feedstock material and application rate under tropical conditions. Our study contributes to elucidating the effects of biochar application to soil on N2O emissions in tropical environments and provides data for future projects that aim to include the practice as a nature-based solution.